"Resistance in the desert: a postcolonial reading of the novel desert by le clézio" (2015)
Literature about the images of the Maghrebian Arabs was usually investigated in postcolonial criticism as either withholding the cultural assumptions produced by Orientalism or proposing an anti-western critique of the hegemonic West. This paper focused on the subversion of the stereotypes of the colonised Maghrebian Arabs in the novel of a contemporary French writer. The study applied postcolonial literary criticism to explore the experiences of representation and difference in relation to the colonial discourse of Orientalism and Fanon’s principles of violence and resistance with a view to establishing the anti-colonial reactions permeating the novel titled Desert. The nomadic Arabs were portrayed as freedom lovers who had to resist the internationally sponsored French army, presented as powerful, barbaric, repressive and oppressive intruders. Europe was demystified, as a hostile land, full of disillusion, brutality and deception. The heroin Lalla epitomised resistance as evidenced in the condemnation of oppression, forced marriage and exile to Europe. The existence of discursive resistance in the novel and the will to give a voice to the marginalized therefore establishes Desert as a postcolonial work, and more particularly a critique of the West from within.